Evolution of the rotational properties and nitrogen surface abundances of B-Type stellar populations. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Granada, A.; Meynet, G.; Ekström, S.; Georgy, C.; Haemmerlé, L.
Abstract: Stellar evolution models predict that rotation induces the mixing of chemical species, with the subsequent surface abundance anomalies relative to single non-rotating models, even during the main sequence (MS) evolution. The lack of measurable nitrogen surface enrichment in MS rotating stars, such as Be stars, has been interpreted as being in conflict with evolutionary models (e.g. Lennon et al .2005 ; Hunter et al .2008 ). In order to have an insight on the kind of ambient we do or we do not expect to find enriched rotating stars, we use our new population synthesis code, to produce synthetic intermediate-mass stellar populations fully accounting for stellar rotation effects, and study their evolution in time.